2011
DOI: 10.1007/s00360-011-0557-3
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound intestinal enzymes of passerine birds: dietary and phylogenetic correlates

Abstract: Bird species exhibit great diversity in digestive tract morphology and enzymatic activity that is partly correlated with the chemical composition of their natural diets. However, no studies have assessed whether the activities of digestive enzymes of the enterocytes correlate with dietary chemical composition data analyzed as a continuous variable at an evolutionary scale. We used a phylogenetically explicit approach to examine the effect of diet on the hydrolytic activity of three digestive enzymes (maltase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 57 publications
0
30
1
1
Order By: Relevance
“…However, the presence of significant inter-specific variation in the level of phenotypic flexibility of digestive physiology suggests that even though young house sparrows are capable of complete compensation for a period of abnormal development of digestive function, we cannot exclude the possibility that such effects are permanent in other species. Strikingly, Ramirez-Otarola and colleagues recently suggested that physiological modification caused by diet composition in the early stages of ontogeny can explain differences between adult passerines in the activity of digestive enzymes (Ramirez-Otarola et al, 2011). The results of our present experiment show that this is not the case at least for house sparrow (and, generally, is unlikely for species that switch diet during ontogeny), but the question is open as to whether it holds for other species.…”
Section: The Evolution Of Flexibility Of Digestive Physiology In Altrcontrasting
confidence: 60%
See 2 more Smart Citations
“…However, the presence of significant inter-specific variation in the level of phenotypic flexibility of digestive physiology suggests that even though young house sparrows are capable of complete compensation for a period of abnormal development of digestive function, we cannot exclude the possibility that such effects are permanent in other species. Strikingly, Ramirez-Otarola and colleagues recently suggested that physiological modification caused by diet composition in the early stages of ontogeny can explain differences between adult passerines in the activity of digestive enzymes (Ramirez-Otarola et al, 2011). The results of our present experiment show that this is not the case at least for house sparrow (and, generally, is unlikely for species that switch diet during ontogeny), but the question is open as to whether it holds for other species.…”
Section: The Evolution Of Flexibility Of Digestive Physiology In Altrcontrasting
confidence: 60%
“…On the other hand, nestlings of the sand martin (Riparia riparia), an aerial insectivore that faces variable food availability, show quite large flexibility of their digestive system (Brzęk and Konarzewski, 2001;Brzęk and Konarzewski, 2004). We hypothesize that the level of flexibility of digestive physiology in passerine nestlings is positively correlated with species-specific variation in feeding conditions, analogous to an evolutionary match between diet composition and the activity of carbohydrate-digesting enzymes observed in adult passerines (Kohl et al, 2011;Ramirez-Otarola et al, 2011). Indeed, some recent studies showed that flexibility in the size of the gastrointestinal tract is related to variability of environmental factors at both the intra-and inter-specific level (Cavieres and Sabat, 2008;Naya et al, 2008).…”
Section: The Evolution Of Flexibility Of Digestive Physiology In Altrmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, it is reasonable to expect that birds should be able to adjust activity of their intestinal digestive enzymes to diet composition. However, the pattern that emerges from previous studies is that in adult passerine birds, there is an inter-specific correlation between diet composition and activity of intestinal carbohydrases, but not proteases Ramirez-Otarola et al, 2011), whereas on an intra-specific level adult passerines are able to adjust activity of intestinal proteases to diet composition, but not carbohydrases (reviewed in McWhorter et al, 2009). In contrast, adult galliforms and anseriforms seem able to modulate activity of their carbohydrases but usually do not modulate proteases (McWhorter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…*Summer results mainly correspond to a previous data published by Ramirez-Otarola et al (2011) and Sabat et al (2013). We completed the sample size by the inclusion of two new specimens of P. fruticeti and five of Z. capensis that were captured in the austral summer of D r a f t …”
Section: Speciesmentioning
confidence: 99%